Patients with cystic fibrosis who could not receive the CFTR modulator treatment: What did they lose in 1 year? - Uytun, Salih; Cinel, Guzin; Polat, Sanem Eryilmaz; Tabakci, Sati Ozkan; Kiper, Nural; Yalcin, Ebru; Dogru, Deniz (Wiley, 2023)
BackgroundCystic fibrosis (CF) is an autosomal recessive disorder caused by CF transmembrane conductance regulator (CFTR) genetic variants. CFTR modulators improve pulmonary function and reduce respiratory infections in CF. This study investigated the clinical and laboratory follow-up parameters over 1 year in patients with CF who could not receive this treatment. MethodsThis retrospective cohort study included 2018 and 2019 CF patient data from the CF registry of Turkey. Demographic and clinical characteristics of 294 patients were assessed, who had modulator treatment indications in 2018 but could not reach the treatment. ResultsIn 2019, patients younger than 18 years had significantly lower BMI z-scores than in 2018. During the 1-year follow-up, forced expiratory volumes (FEV1) and FEV1 z-scores a trend toward a decrease. In 2019, chronic Staphylococcus aureus colonization, inhaled antipseudomonal antibiotic use for more than 3 months, oral nutritional supplement requirements, and oxygen support need increased. ConclusionsPatients who had indications for modulator treatments but were unable to obtain them worsened even after a year of follow-up. This study emphasized the importance of using modulator treatments for patients with CF in our country, as well as in many countries worldwide.
Keywords: body mass index; CFTR modulator; cystic fibrosis; forced expiratory volume; z-scores